1997
DOI: 10.1016/s0022-5347(01)64778-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional Intactness of Stimulatory and Inhibitory Autocrine Loops in Human Renal Carcinoma Cell Lines of the Clear Cell Type

Abstract: Clear cell RCCs exhibit a complex and heterogeneous expression pattern for various growth factors and their receptors. Growth factor secretion and intact signal transduction pathways in most clear cell RCCs facilitate an intricate modulation of RCC growth by autocrine and paracrine interactions between tumor cells and host tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Other investigators have examined human RCC lines and identified alterations in the expression of TGFb signaling pathway intermediaries such as TBR2 and the Smads (Engel et al, 1999), but these observations have not been validated in the clinical biology of RCC. Ramp et al (1997b) found that TBR3 mRNA was expressed in only 1/13 RCC cell lines examined. To our knowledge, few studies have methodically examined the expression of all three TBRs in patient samples at the protein and mRNA level, in an effort to correlate TBR expression to disease-specific states of RCC (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Other investigators have examined human RCC lines and identified alterations in the expression of TGFb signaling pathway intermediaries such as TBR2 and the Smads (Engel et al, 1999), but these observations have not been validated in the clinical biology of RCC. Ramp et al (1997b) found that TBR3 mRNA was expressed in only 1/13 RCC cell lines examined. To our knowledge, few studies have methodically examined the expression of all three TBRs in patient samples at the protein and mRNA level, in an effort to correlate TBR expression to disease-specific states of RCC (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…An elevated amount of insulin-and IGF-1 receptor expression with increased specific autophosphorylation and tyrosine-kinase activity in surgically resected samples has been reported (13). In contrast, others found no expression of IGF-1 and its receptors in RCC cell lines (14). Therefore, the role of IGF-1 in RCC is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…RCC cell lines have been shown to be capable of synthesizing several of such cytokines, including TNFa (Gogusev et al 1993). In addition, inhibitory autocrine loops involving cytokine secretion have been demonstrated in RCC (Ramp et al 1997). While the exact mechanisms of secretion for such cytokines remain largely unknown, Pgp has recently been shown to be involved in the transport of IL-2, IFNc and IL-4 (Drach et al 1996).…”
Section: Discussionmentioning
confidence: 99%